The Story of the Liberation of Mecca in Surah An-Nasr and Its Effects (A Stylistic Study of the Quran) - Wahyuni Handayani (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Stories are a means of conveying theological and humanist messages to society, and even contain linguistic and artistic elements. One of them is the story of the liberation of the city of Mecca contained in the Koran surah an-nasr. This letter consists of three verses. Surah an-nasr itself means help. Therefore, researchers feel interested in further analyzing the linguistic problems that exist in it. The purpose of this study is to reveal the linguistic phenomena in the sura. The theory used in this research is Stylistics theory. The reason for choosing this theory is because stylistics covers all aspects of language, both in terms of phonology, morphology, semantics, syntax, and imagery. this research is a library research using qualitative methods. The results of this study indicate that there are five language styles based on the level of stylistic analysis. including: 1) the phonological level: there is a dominant sound that dominates the mahmus sound. This implies the clarity and truth of Allah's help in victory for believers. 2) morphological level: the selection of fi'il madhi ja'a which carries a special meaning behind it. 3) syntactical level: there are isim ma'rifah and nakirah, which are unique in terms of syntax. 4) semantic level: the choice of the words millah and ja'a is considered appropriate and is part of their semantic peculiarities. 5) imagery level: this surah contains an element of building beauty, namely isti'arah makaniyah